Aesthetic Surgical Procedures- Is It A Matter of Age? - GAUR, SHIVANGI; M, MADHULAXMI; O R, HEMAVATHY (The journal of contemporary issues in business and government, 2020)
Face is the seat of an individual’s identity. Hence treatment plan and execution of corrective esthetic surgeries are challenging. The average age at which patients become self- aware of dentofacial deformities and seek professional help is usually in the second decade of life when they begin to develop a sense of individualistic identity to integrate into the society. However, it is observed that individuals in the older age groups are seeking treatment for correction of dentofacial deformities. The aim of this study was to identify the age at which individuals report for orthognathic surgery. For the purpose of this study, data collection was done retrospectively from the hospital archives for patients undergoing orthognathic surgery during a period of ten months from June 2019 to March 2020. In our study it was observed that despite differences in chief complaints, 54.17% females and 45.83% males seek jaw corrective procedures. Though the association between age of patients and osteotomy procedure was not of statistical significance (p=0.470 > 0.05), there was a substantial increase in those seeking treatment in the fourth decade of life (16.67%) implying a marked clinical significance. This increase is due to the multidisciplinary team involved in functional rehabilitation of patients in this age group.